Review of the judicial practice of the Serbian Supreme Court and courts of appeal in family matters - Stojanović Nataša (Zbornik Radova Pravnog Fakulteta u Nišu)
The Family Act of the Republic of Serbia was adopted in 2005 and has been used in practice for almost 20 years. This is an opportunity to review its application in practice, especially by observing the judicial practice of the Serbian Supreme Court and the Courts of Appeal. In this paper, the author provides an overview of the judicial practice of these courts in family matters from the moment when the Family Act entered into force to date. In particular, the author focuses on family law institutes whose application has proved to be most controversial in practice. These family law institutes are: the legal status of cohabitation (extramarital union), establishing the origin of a child, deprivation of parental rights, maintenance, property relations in the family, and domestic violence. Using primarily the content analysis method (court decisions) as well as the dogmatic, normative and legal history methods, the author analyzes several selected judgments of the Supreme Court and Courts of Appeal in the Republic of Serbia. The analysis is aimed at identifying and emphasizing the differences in viewpoints of these courts on controversial family matters, which ultimately indicates the disparities and inconsistent practice of the same court instance in almost identical family law cases and an unequal treatment of parties in these proceedings. In the author's opinion, a large number of controversial family matters in the domestic judicial practice is an actual indicator of the decline and disintegration of the family as the basic cell of the society. From the legal point of view, this trend may be reduced by "eliminating" the observed uncertainties and inaccuracies in the Serbian Family Act, providing guidelines and detailed explanations on the applicable legal standards, and filling in all the legal gaps observed in legal theory and judicial practice. In addition to the existing legal mechanisms, it is necessary to create a new mechanism which would contribute to a more qualitative harmonization of the judicial practice in the field of civil matters in the Republic of Serbia.